Earnings Quality Research: Trend, Recent Evidence and Future Direction - Fonou Dombeu, Nyanine Chuele; Nomlala, Bomi Cyril (International Review of Management and Marketing, 2023)
This paper provided an overview of earnings quality research by assessing whether area of future research and challenge identified in prior studies have been addressed in the literature. Specifically, the study discussed two areas of earnings quality that have received attention in the last decade: the impact of fair value accounting on earnings quality and the models used to measure accrual quality. A comment on earnings quality during the COVID-19 pandemic is also provided. The study revealed that fair value accounting affect earnings quality and the empirical results on the effect of fair value on earnings quality are mixed and depend on the environment in which the firm operates. The study also showed that, earlier models used to measure accrual quality are still currently been used and the literature has evolved to take into consideration the innate and discretionary components of earnings quality. However, it is still not clear whether the models used to separate earnings quality into its components are effective. This paper contributes to knowledge by synthesizing new insight into the current state of knowledge on some aspects of earnings quality research. The study further identified unanswered questions in the field, which provides direction for future studies.